Beyond HAART: unveiling the reality of antiretroviral therapy knowledge among pregnant women living with HIV in Kaduna State, Nigeria - Oludare ‘Sunbo Adewuyi; Joseph Yaria; James Aigboje Orevba; Patrick Nguku; Magbagbeola David Dairo (Scientific Reports)
Abstract To ensure the prevention of mother-to-child-transmission of HIV (MTCT), 81% of pregnant women received antiretroviral therapy (ART) in 2021 worldwide. Despite the global efforts to prevent MTCT of HIV, significant knowledge gaps persist among these women including a lack of basic knowledge of HIV and ART. This study aimed to determine the levels of HIV knowledge, knowledge of ART, and attitude toward ART in HIV-positive pregnant women in Kaduna State. It was a hospital-based, cross-sectional study among 318 HIV-positive pregnant women attending antenatal care in the nine selected hospitals using a three-stage sampling technique. Data was collected using the Open Data Kit. Up to 54.4% had a fair knowledge of ART while 75.4% of the respondents had good knowledge of HIV, and up to 98.6% had a positive attitude towards ART. Knowledge of ART and attitude to ART are positively influenced by receiving multiple counselling (p = 0.031, aOR = 6), being on ART for ≥ 2 years (p = 0.021, aOR = 6); and not taking unprescribed medications (p = 0.047, aOR = 17) respectively. Sustained, focused counselling and patient education are necessary to establish and optimise the required adherence in this group. Also, implement clear task-sharing strategies for health personnel to provide tailored services.